Dynamic Axial Crushing Of Empty Hexagonal Tube - SAID, MD RADZAI (2012)
The experimental result of empty hexagonal tube subjected to dynamic loading is reported and compared with the previous researchers. The type and final mode of deformation is also studied and compared with FEA. Good agreement is obtained between FEA and experiments for both mean loud and plastic fold length. The dynamic mean load is about 1.5 times that of the quasi-static value.